Life history responses of two ephemeral plant species to increased precipitation and nitrogen in the Gurbantunggut Desert - Chen, Yanfeng; Zhang, Lingwei; Shi, Xiang; Liu, Huiliang; Zhang, Daoyuan (PeerJ, 2019)
Precipitation change and nitrogen deposition are not only hot topics of current global change but also the main environmental factors affecting plant growth in desert ecosystems. Thus, we performed an experiment of increased precipitation, nitrogen, and precipitation plus nitrogen on the ephemeral annual species Nepeta micrantha and Eremopyrum distans in the Gurbantunggut Desert. We aimed to determine the life history responses of N. micrantha and E. distans to environment changes, and the germination percentage of the offspring (seeds) was also tested in the laboratory. The results showed that increased nitrogen and precipitation plus nitrogen increased the growth of both plant species, whereas increased precipitation inhibited the growth of N. micrantha but increased the growth of E. distans. This differential response of these two species to precipitation and nitrogen also affected the germination of their offspring. In response to increased nitrogen and precipitation plus nitrogen, the germination percentage of the offspring produced by two species decreased in conjunction with the plants exhibiting high reproduction, which may prevent overcrowding during the following year; however, the N. micrantha plants produced more nondormant offspring in conjunction with low reproduction under relatively greater amounts of precipitation, and N. micrantha offspring could occupy their habitat via rapid germination in suitable environments. Therefore, with increased precipitation and nitrogen deposition, these differences in offspring dormancy may affect their ecological niche in the community.
Keywords: Climate change; Ephemeral plant; Eremopyrum distans; Gurbantunggut Desert; Increased precipitation; Interaction; Nepeta micrantha; Nitrogen deposition